ANALISIS KEWENANGAN NOTARIS PENGGANTI DALAM PENERBITAN SALINAN & MINUTA AKTA UNTUK KETERANGAN HUKUM DI PENGADILAN - Laiskodat, Pippo Inzaghi Dasan (Fakultas Hukum Universitas Narotama, 2024)
The authority of a substitute notary in the issuance of copies and minutes of deeds for legal testimony in court and police investigations is an important issue in the legal field that requires in-depth understanding. This research aims to analyze the scope and limits of the authority of a substitute notary in the context of issuing these legal documents. The research method used is a literature study to collect information and data related to the authority of substitute notaries, as well as analyzing various regulations and related court decisions. The results of the analysis show that the authority of a substitute notary has clear limitations in the issuance of copies and minutes of deeds for legal purposes in court and police investigations. Factors such as statutory provisions, notary code of ethics, as well as court decisions are the main considerations in determining the authority of a substitute notary in certain situations. This research provides a better understanding of the role of substitute notaries in the broader legal context, as well as the relevant legal implications in notarial practice in Indonesia. Keywords: Authority, Substitute Notary, Copy, Deed Minute, Court